ON THE HELP OF MOTIVATION IN LEARNING ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Motivation in teaching is one of the foundations of successful mastery of the subject. In this article, the author examines the approaches of domestic and foreign specialists in the field of psychological and pedagogical aspects of teaching foreign languages. Motivation to study English in educational establishments is defined as a transitional concept, that is, it depends on both the students themselves and the teacher. The paper focuses on ways to form and maintain students' interest in the English language. The author pays attention to both the psychological features of the teacher's work with students, as well as types of tasks that contribute to increasing the motivation of students.